Use of whole genomic sequencing to detect New Delhi metallo-B-lactamase (NDM)-producing Escherichia coli outbreak associated with endoscopic procedures - Suleyman, Geehan; Shallal, Anita; Ruby, Abigail; Chami, Eman; Gubler, Jenny; McNamara, Sara; Miles-Jay, Arianna; Tibbetts, Robert; Alangaden, George (Infection control and hospital epidemiology, 2024)
Whole-genome sequencing (WGS) has emerged as an alternative genotyping tool for outbreak investigations in the healthcare setting. We describe the investigation and control of a New Delhi metallo-B-lactamase (NDM)-producing cluster in Southeast Michigan. Michigan Bureau of Laboratories identified several closely related NDM-producing isolates with WGS. An epidemiologic investigation, including case-control study, assessment of infection control practices, and endoscope culturing, was performed to identify source of transmission. Targeted screening of potentially exposed patients was performed following identification of probable source. Between July 2021 and February 2023, nine patients were identified. Phylogenetic analysis confirmed the isolates were closely related with less than 26 single nucleotide polymorphism (SNP) differences between isolates, suggesting an epidemiological link. Eight (89%) patients had a duodenoscope and/or gastroscope exposure. Cases were compared with 23 controls. Cases had significantly higher odds of exposure to duodenoscopes (odds ratio 15.0; 95% CI, 1.8-142.2; = .015). The mean incubation period, estimated as date of procedure to positive index culture, was 86 days (range, 1-320 days). No lapses in endoscope reprocessing were identified; NDM-producing was not recovered from reprocessed endoscopes or during targeted screening. No additional cases were identified after removal of implicated gastroscopes and replacement of duodenoscope with disposable end caps. In this investigation, WGS was utilized to identify transmission of an NDM-producing outbreak associated with endoscope exposure. Coupled with epidemiologic data, WGS can facilitate outbreak investigations by rapidly identifying linked cases and potential sources to prevent further transmission.